Mobility Potential and the Quality of Life in Working-Class Lowell, Massachusetts: The French Canadians ca. 1870 - Early, Frances H. (Labour / Le Travail, 1977)
Discusses the quality of life amongst French-Canadians living in Lowell, Massachusetts in 1870. Explores the development of a working-class community in the mill town after the American Civil War, in particular the migration of French-Canadians into the community. Analyzes the occupations of the French-Canadian immigrants, concluding that the vast majority were working-class with low mobility potential. Examines the living conditions of working-class people at the time. Argues that life was difficult for French-Canadian immigrants in New England during this period.